A synthesised framework of eco‐industrial park transformation and stakeholder interaction. (5th April 2022) - Dai, Yuxi; Day, Steven; Masi, Donato; Gölgeci, Ismail
Abstract: Eco‐industrial parks (EIPs) combine the concepts and principles of industrial ecology (IE) and industrial symbiosis (IS) to enable environmentally‐friendly industrial manufacturing capacity. The current reality is that many EIPs are developed from ageing industrial parks (IPs). However, how such EIP transformation projects are managed by diverse public and private stakeholders is largely unknown. This study summarises the results of a systematic literature review ( n  = 61) to identify a five‐stage process of EIP transformation. Five key stakeholders and influencing factors are identified, and drawing on process theory, a framework is developed that highlights how these stakeholders work together over time. While this study serves as an overview of the body of knowledge on the business and social aspect of EIP transformation, the main contribution of this work is the propositions on the interactions and order of stakeholders embedded in the framework, which can guide future research especially on the early stages of EIP transformation. In practice, EIP project managers can judge the stage of the project based on the project status and work back from actions entities undertake to progress the project systematically.